Inferring shifts in tree species distribution using asymmetric distribution curves: a case study in the Iberian mountains - Urli, Morgane; Delzon, Sylvain; Eyermann, Audrey; Couallier, Vincent; GARCÍA-VALDÉS, Raúl; Zavala, Miguel Angel; Porté, Annabel J (Journal of Vegetation Science, 2013)
Questions The objectives of this study were to examine altitudinal shifts in tree species distributions over one decade to quantify the potential for tree migration. Location Spain. Methods We analysed presence–absence data using two successive surveys of the Spanish Forest Inventory in five Fagaceae tree species (two temperate: Fagus sylvatica and Quercus petraea, one sub-Mediterranean: Q. faginea and two Mediterranean: Q. suber and Q. ilex) in two mountain ranges (the Pyrenees and the Iberian system). Half of the fitted altitudinal distributions were skewed and required use of an asymmetric model for unbiased estimates of optimum altitude and changes in the probability of presence along the altitudinal gradient. For each species and mountain range, shifts were considered to have occurred when the difference in optimum altitude was significant or when differences in probability of occurrence between the two surveys demonstrated the occurrence of colonization or extirpation events. Results Overall, depending on species and mountain range, shifts in optimum altitude ranged between −34 m and +181 m. The altitudinal distribution of the Mediterranean species at the core of their latitudinal distribution range presented no sign of change. For the temperate and sub-Mediterranean Fagaceae species, the patterns demonstrated the existence of distribution changes over a 10-yr period. The largest, although not statistically significant, upward shift in optimum altitude was observed for Q. petraea in the Iberian system. More interestingly, its distribution indicated colonization events at higher altitudes. For Q. faginea in the Pyrenees, the shift in optimum altitude was the second largest and statistically significant, and was associated with large extirpation events at the lower altitudes. No evidence of shifts was observed for F. sylvatica. Conclusion This work demonstrates that changes in altitudinal distribution could occur over a 10-yr time period for tree species located at the southern limit of their distribution, such as some temperate and sub-Mediterranean oaks, whereas no movement was detected for Mediterranean oaks in the core of their distribution area.
Keywords: Altitudinal distribution; Fagus; FOREST; model; Optimum; Quercus

A model to account for variations in production in southern Spain - García-mozo, Herminia; Dominguez-vilches, Eugenio; Galán, Carmen (Annals of Agricultural and Environmental Medicine, 2012)
One of the characteristics of holm-oak acorn production is its high variability among individuals and years. To examine the main causes of this fact, a study was conducted from 1998-2010 in a natural area of holm-oak in southern Spain, where floral phenology, fruit production, fruit size, airborne pollen emission and meteorology factors were analyzed with the ultimate aim of developing a model for forecasting holm-oak yield. Pollen emission during flowering season was the main factor determining the final acorn harvest, but also some meteorological variables played an important role in explaining acorn crop variations, especially humidity and temperature during the months of April and September. The reliability of the proposed model was externally validated using data not included in its construction; validation yielded acceptable results, with a minimum error of estimation. Our results appear to be very useful for planning cropping and pig feeding strategies. Further research could extend the use of airborne pollen counts in forest studies relating to anemophilous species, in order to optimize agricultural policies.
Keywords: acorn production; Aerobiology; Holm oak; model; oak forest; Phenology; pollen; quercus ilex subsp. ballota

A conceptual model of sprouting responses in relation to fire damage: an example with cork oak (Quercus suber L.) trees in Southern Portugal - Moreira, Francisco; Catry, Filipe; Duarte, Inês; Acácio, Vanda; Silva, Joaquim Sande (Plant Ecology, 2008)
The sprouting response types of 1,151 cork oak (Quercus suber) trees one and half years after a wildﬁre in southern Portugal were characterised. It was hypothesised that different response types should occur according to the following conceptual model: an increased level of damage (ﬁre severity) on a sprouting tree that suffered a crown ﬁre was expected to be reﬂected in a sequence of four alternative events, namely (a) resprouting exclusively from crown, (b) simultaneous resprouting from crown and base, (c) resprouting exclusively from base and (d) plant death. To assess whether the level of expected damage was inﬂuenced by the level of protection from disturbance, we explored the relationships between response types and tree size, bark thickness and cork stripping, using an informationtheoretic approach. The more common response type was crown resprouting (68.8% of the trees), followed by plant death (15.8%), simultaneous resprouting from crown and base (10.1%) and basal resprouting (5.3%). In agreement with the conceptual model, trees which probably suffered a higher level of damage by ﬁre (larger trees with thinner bark; exploited for cork) died or resprouted exclusively from base. On the other hand, trees that were well protected (smaller trees with thicker bark not exploited for cork) were able to rebuild their canopy through crown resprouting. Simultaneous resprouting from the crown and base was determined mainly by tree size, and it was more common in smaller trees.
Keywords: apical dominance; Mediterranean; model; mortality; resource allocation; resprouting; severity